A STUDY FOR VISION OF AGRICULTURAL EXTENSION WORK TO REDUCE THE DEGRADATION OF AGRICULTURAL SOILS IN MATROUH GOVERNORATE - Samia Mahrous (Arab Universities Journal of Agricultural Sciences, 2014)
The recent study aims to: identify a vision of agricultural extension work to reduce the degradation of agricultural soils, and determine the relationship between the independent variables studied, and the degree of vision of agricultural extension work to reduce the degradation of agricultural soils and identifying the farmer's suggestion to reduce Soil degradation. The study was conducted in Siwa Oasis in Matrouh Governorate. Data were collected through the personal interview with a systematic random sample of 148 farmers in Siwa Oasis using a questionnaire. Frequencies, per- centages and simple correlation coefficient (Pearson) were utilized to present and analyze data. The most important findings were: 29.4% of the respondents had a low level knowledge of reducing Soil degradation technical recommendation. The fending also indicated significant correlation at 0.01 level between the degree of agricultural extension work vision to reduce Soil degradation and the following variables: the respondent's education level, the degree of tribal leadership and the degree of tribal affiliation. There were significant correlations at 0.05% level between the same dependent variable and: area agricultural holdings and period of experience work in agricultural. There were non significant correlation between dependent variable and: age and size of the possession of agricultural animals.